Introduction to Studies on Pre-Capitalist Modes of Production: Debates, Controversies and Lines of Argument - Da Graca, Laura Cecilia (2015)
This book analyses a variety of historical problems related to pre-capitalist societies and explores both the concept and the range of modes of production arising from the writings of Marx and Engels and subsequent Marxist elaborations. There are differing assessments of the Marxist tradition on pre-capitalist modes of production, which reflects the debate within historical materialism with regard to the potential or the inconsistencies of some of the categories proposed by Marx. The critique of these categories, or the perception that they are insufficient, has led to the elaboration of new concepts such as the domestic mode of production proposed by Claude Meillassoux aimed at the analysis of agrarian lineage societies, Marshall Sahlins’s homonymous concept covering hunter-gatherer societies, or Chris Wickham’s recently proposed peasant mode of production geared to the analysis of agrarian societies without systematic surplus extraction.